Effects of Carbon Impurity in Monocrystalline Silicon on Electrical Properties and the Mechanism Analysis of PIN Rectifier Diodes - Xinli Sun; Hui Guo; Yuming Zhang; Xingpeng Li; Zhen Cao (IEEE Access, 2021)
Carbon impurities are common defects in monocrystalline silicon and have negative effects on the electrical performance of electronic devices. In the present work, the effects of carbon impurities in monocrystalline silicon on the electrical properties of PIN rectifier diodes with different carbon concentrations were investigated by electrical performance tests, anisotropic preferential etching, Fourier-transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), and energy-dispersive spectroscopy (EDS). It was found that with the increasing carbon concentration, the reverse leakage current (IR) increased rapidly, the time of reverse recovery (TRR) and the ratio of the average reverse withstand voltage to the theoretical value decreased rapidly, and the forward voltage drop ( $V_{f}$ ) increased significantly. Further, with the rising carbon concentration, bulk oxidation-induced defects (B-OSF) changed from dislocation-dominated to stacking fault-dominated and the stacking fault length increased gradually. [ $C_{i}-O_{i}$ ] carbon centers of interstitial carbon and interstitial oxygen with a wide absorption band were detected by FTIR. The existence of stacking dislocation defects and carbon-oxygen complexes [ $C_{i}-O_{i}$ ] was confirmed by TEM and EDS. It was pointed out that substitutional carbon ( $C_{s}$ ) captured interstitial silicon atoms, changed into interstitial carbon ( $C_{i})_{}$ in the silicon substrate, and formed [ $C_{i}-O_{i}$ ] complexes of interstitial carbon and interstitial oxygen after high-temperature diffusion, and these complexes acted as heterogeneous nucleation centers to promote the formation and growth of oxygen precipitation. Due to the volume strain energy, interstitial silicon atoms and dislocations were continuously released to promote oxygen atoms during the growth process of carbon-oxygen complexes. The formation and growth of B-OSF defects caused the “impurity piercing pipe” effect. These defects acted as defect recombination centers and deteriorated the electrical performance of the PIN rectifier diodes.